2024
DOI: 10.1182/bloodadvances.2023010815
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and impact of diabetes on survival of patients with multiple myeloma in different racial groups

Urvi A. Shah,
Erin Moshier,
Andriy Derkach
et al.

Abstract: Multiple myeloma (MM) is twice as common in Black individuals compared to White, and diabetes mellitus (DM) disproportionately affects Black patients. While numerous studies have shown a correlation between DM and MM, this has not been studied in the context of race and in vivo mechanisms. We conducted a retrospective clinical study of 5383 patients with MM of which 15% had DM (12% White and 25% Black). Multivariable Cox models showed reduced overall survival (OS) for patients with DM (HR 1.27; 95% CI 1.11, 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Although DM might be associated with the development of MM [16] and DM may be an adverse prognostic factor for overall survival in patients with MM [17], data linking DM and MGUS are limited, with conflicting conclusions due to the overlapping effect of obesity [18]. A population-based matched case-control study in Sweden, with 94,579 cases and 368,348 controls, aimed to examine the association between DM and plasma cell dyscrasias as well as lymphoproliferative disorders [19].…”
Section: Diabetes Mellitusmentioning
confidence: 99%
“…Although DM might be associated with the development of MM [16] and DM may be an adverse prognostic factor for overall survival in patients with MM [17], data linking DM and MGUS are limited, with conflicting conclusions due to the overlapping effect of obesity [18]. A population-based matched case-control study in Sweden, with 94,579 cases and 368,348 controls, aimed to examine the association between DM and plasma cell dyscrasias as well as lymphoproliferative disorders [19].…”
Section: Diabetes Mellitusmentioning
confidence: 99%
“…In this issue of Blood Advances, Shah et al report a retrospective clinical study evaluating the impact of diabetes and obesity on survival among patients with multiple myeloma from 2 academic medical centers. 1 This study is among the first to evaluate the association separately in Black and White patients. Over a median follow-up of 4.6 years, the data showed that patients with multiple myeloma and preexisting diabetes had worse overall survival compared to patients with nondiabetic conditions, whereas patients with elevated body mass index (BMI ≥25 kg/m 2 ) had improved overall survival compared to those with BMI <25 kg/m 2 .…”
mentioning
confidence: 99%
“…In contrast, obesity was associated with better overall survival in Black patients, but not in White patients. 15 Nevertheless, bortezomib is a component of standard MM treatment across lines of therapy, 16 and its use remains frequent in the real-world setting. Bortezomib dosing has evolved over the last few years from twice-weekly use, as described in this study, to weekly use.…”
mentioning
confidence: 99%